TEORI BELAJAR & PEMBELAJARAN AL-QUR’AN HADIS DI TINGKAT MADRASAH IBTIDAIYAH (MI) DAN MADRASAH TSANAWIYAH (MTS) - Zuairiyah Zuairiyah; Ari Sabila Najwa; Badrus Zaman (Tasyri’: Jurnal Tarbiyah – Syari’ah Islamiyah, 2025)
This study aims to analyze learning theories relevant to Qur’an and Hadith teaching in Madrasah Ibtidaiyah (MI) and Madrasah Tsanawiyah (MTs). The method used is library research with a descriptive-analytical literature review approach. Data were collected from Google Scholar, Semantic Scholar, and national journals indexed in Sinta and Garuda. Thematic analysis was employed through coding, categorization, and synthesis. The findings indicate that behaviorist theory supports memorization practice, cognitive theory aids text comprehension, constructivist theory fosters active student engagement, and humanistic theory emphasizes character formation. The integration of these theories enhances Qur’an and Hadith learning, making it not only memorization-oriented but also focused on understanding and applying Islamic values.